The Influence of ROA, BOPO and CAR on The Profit Sharing Rate of Mudharabah Deposits at Bank Muamalat Indonesia 2012-2021 - Tarmidi, Aurellya Az-zahra (Institut Agama Islam Sunan Giri Ponorogo, 2022)
The development of the Islamic economy is currently quite rapid, marked by the development of Islamic financial institutions. The development of Islamic financial institutions, especially Islamic banking is quite extensive until now. This study aims to examine the effect of the ratio of return on assets (ROA), Operational Expenses on Operating Income (BOPO) and Capital Adequacy Ratio (CAR) on the Profit Sharing Rate of Mudharabah Deposits at Bank Muamalat Indonesia for the period 2012-2021. This research is a quantitative research using multiple linear regression analysis technique as statistical analysis. The results of this study indicate that the variable X, namely ROA, BOPO and CAR has no effect on the Profit Sharing Rate for Mudharabah Deposits where the F sign value is 0.12. Whereas in the partial test ROA and BOPO have no effect on the Profit Sharing Rate for Mudharabah Deposits where the sign value of t is 0.15 and 0.58. The coefficient of determination shows an R-Square of 58%. So it can be concluded that the diversity of variable y can be explained by variable x by 58%. Based on the analysis the value of ROA, BOPO and CAR ratio has no effect on the Profit Sharing Rate for Mudharabah.